2017
DOI: 10.1209/0295-5075/118/50008
|View full text |Cite
|
Sign up to set email alerts
|

Virtual black holes from the generalized uncertainty principle and proton decay

Abstract: We investigate the formation of virtual black holes in the context of generalized uncertainty principle (GUP), as a mediator for a proton decay process which is forbidden by the standard model. Then, we calculate the lower bounds of the GUP deformation parameter by the experimental bound on the half life of the proton.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…As one example, a neutrino might be absorbed by the black hole, with the black hole subsequently evaporating/decaying to produce new particles altogether, conserving only energy, charge and angular momentum (as per the no hair theorem [36]) but not baryon or lepton number. Such processes have been proposed as a source of proton decay, where the constituent quarks of the otherwise stable proton are absorbed by the VBH and reemitted as other particles [37,38]. Heuristically, the neutrino may be viewed as being stochastically absorbed and (possibly) re-emitted by these VBH encounters during propagation, with this stochasticity potentially resulting in decoherence.…”
Section: Decoherence From Stochastic Perturbationsmentioning
confidence: 99%
“…As one example, a neutrino might be absorbed by the black hole, with the black hole subsequently evaporating/decaying to produce new particles altogether, conserving only energy, charge and angular momentum (as per the no hair theorem [36]) but not baryon or lepton number. Such processes have been proposed as a source of proton decay, where the constituent quarks of the otherwise stable proton are absorbed by the VBH and reemitted as other particles [37,38]. Heuristically, the neutrino may be viewed as being stochastically absorbed and (possibly) re-emitted by these VBH encounters during propagation, with this stochasticity potentially resulting in decoherence.…”
Section: Decoherence From Stochastic Perturbationsmentioning
confidence: 99%
“…This result is obtained without assumptions outside GR and quantum theory.Virtual black holes were also studied in third quantised formalism of canonical quantum gravity [6], in dilatorn gravity theories ? ?, and in other alternative theories as in generalised uncertainty principle and their phenomenological implications in proton decay [2] and higher spin theories from Teukolsky equations [15]. Virtual black holes are also important in understanding the black hole information paradox [5], for example, it has been shown that the S-matrix of scattering processes by virtual black hole is incoherent [10], leading to a possible indication that information paradox could be resolved by studying the phenomenology of scattering by virtual black holes [9].…”
Section: The Space-time At the Plank Scalementioning
confidence: 99%
“…However, such consideration would leave a tight window for other GUT models, in particular, like those involving strings and branes [98], variations of SO(10) group [99], or by leptoquarks models [100] which shows an increasing interest, due to recent findings related to the anomalies in B-meson decays at the LHCb experiment [101]. Moreover, the proton could decay via VBH, and the lifetime of this decay can be estimated from the relation in D dimensions [80,102]…”
Section: Introductionmentioning
confidence: 99%